A novel terrain adaptive omni-directional unmanned ground vehicle for underground space emergency: Design, modeling and tests. (February 2021) - Qi, Lingfei; Zhang, Tingsheng; Xu, Kai; Pan, Hongye; Zhang, Zutao; Yuan, Yanping
Highlights: A novel terrain adaptive unmanned ground vehicle is proposed. This unmanned ground vehicle possesses the function of omni-directional steering. This proposed vehicle is used for city underground space emergency detection. Experimental results show that the proposed system has a good performance. Abstract: With the striking development of underground space of smart cities, the detection and emergency treatment of underground space has become more and more important. At a dangerous search and rescue scene, an unmanned ground vehicle can perform the tasks instead of a rescue worker such as incident localization, hazardous material identification, toxic gas collection, and security surveillance. In this paper, we present a novel terrain adaptive omni-directional unmanned ground vehicle (TAOUGV) for search and rescue missions in underground space. The proposed system consists of three main parts: obstacle detection, terrain adaptive mechanical module and control module. In the first part, a binocular camera system and an ultrasonic sensor are used to detect obstacles as the TAOUGV is moving. Using a dilation and erosion algorithm, we can obtain all obstacle information including distance, width and height in front of the TAOUGV on condition of complicated environment. In the second step, the terrain adaptive mechanical mechanism with the minimum number of wheels can navigate passively through rough terrain, climb obstacles actively through a lifting unit, and utilize omni-directional motion for avoiding obstacles. Finally, the control module controls the central controller to implement mode selection such as passive crossing mode, active climbing mode, omni-directional motions, and sensor control for hazardous material and toxic gas collection. The simulation and testing results demonstrate the feasibility of the proposed TAOUGV for use in an underground space emergency detection.